Dynamic simulation and 2D multiple scales and multiple sources within basin geothermal field. (1st January 2013) - Li, Xing; Wu, Chonglong; Cai, Suihua; Han, Huan; Zhang, Zhiting; Liu, Zhifeng
In order to accurately describe the geothermal field within a basin, it is necessary to divide it into the normal geothermal field and additional geothermal field. For the accuracy by describing of the additional geothermal field, grids need to be increased. Traditional unequal interval difference method can be used to solve this problem, which has to increase grids within the unnecessary area, so as to make the calculated amount larger. Moreover, the calculation cannot be operated by the computer when there are several anomalous areas. This paper has solved simple difference method by focusing on local grids increased by introducing the method of virtual points. The comparison and analysis of the method show clearly that its precision is within a reasonable error range, whereas the calculation amount decreases obviously. The application of this method into the paleo-thermal field simulation in Dongying Depression, Shandong Province, China is effective in the hybrid simulation of the multiple scales geothermal field model within this area successfully.